Monetary union and stabilization policy in the European Community - PARKIN, M. (PSL Quarterly Review, 2014)
A plan for European Monetary Union was recently proposed based on the issue of a parallel European currency, the acceptance of which would be established by a market process, not by official edicts and which would be managed to achieve stable European-wide prices. This paper examines the desirability of, and problems associated with this particular approach. It represents yet a further attempt to show that the anti-union arguments are either wrong or they are positive, not normative propositions which lead to the prediction that union will not occur and do not lead to the prescription that it shouldn’t. The inflation records of the individual countries are first examined and the reasons for national differences in that rate are analysed. Then the implications of monetary union are analysed. Finally, the political objections to monetary union are considered. JEL: F36, F33